Novel acridine-based thiosemicarbazones as 'turn-on' chemosensors for selective recognition of fluoride anion: a spectroscopic and theoretical study. Issue 7 (4th July 2018) - Isaac, Ibanga Okon; Munir, Iqra; al-Rashida, Mariya; Ali, Syed Abid; Shafiq, Zahid; Islam, Muhammad; Ludwig, Ralf; Ayub, Khurshid; Khan, Khalid Mohammed; Hameed, Abdul
Abstract : New thiosemicarbazide-linked acridines 3a–c were prepared and investigated as chemosensors for the detection of biologically and environmentally important anions. The compounds 3a–c were found selective for fluoride (F − ) with no affinity for other anions, i.e. − OAc, Br −, I −, HSO4 −, SO4 2−, PO4 3−, ClO3 −, ClO4 −, CN − and SCN − . Further, upon the gradual addition of a fluoride anion (F − ) source (tetrabutylammonium fluoride), a well-defined change in colour of the solution of probes 3a–c was observed. The anion-sensing process was studied in detail via UV–visible absorption, fluorescence and 1 H-NMR experiments. Moreover, during the synthesis of acridine probes 3a–c nickel fluoride (NiF2 ), a rarely explored transition metal fluoride salt, was used as the catalyst. Theoretical studies via density functional theory were also carried out to further investigate the sensing and anion (F − ) selectivity pattern of these probes.